2002
DOI: 10.1614/0043-1745(2002)050[0622:gfsfoa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Giant foxtail (Setaria faberi) outcrossing and inheritance of resistance to acetyl-coenzyme A carboxylase inhibitors

Abstract: Gene flow via pollen and inheritance of acetyl-coenzyme A carboxylase (ACCase) inhibitor resistance in giant foxtail have not been previously characterized. Therefore, experiments were conducted to quantify outcrossing rates and flowering periods of giant foxtail accessions resistant or susceptible to ACCase inhibitors and to determine the inheritance pattern of gene(s) that confer resistance. In greenhouse experiments, outcrossing rates between resistant and susceptible parents ranged from 0.24 to 0.73%, as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…), annual ryegrass (Tal & Rubin ; Tardif et al . ), giant foxtail (Volenberg & Stoltenberg ), green foxtail ( Setaria viridis ) (Stilkowski ) and foxtail millet (Wang & Darmency ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), annual ryegrass (Tal & Rubin ; Tardif et al . ), giant foxtail (Volenberg & Stoltenberg ), green foxtail ( Setaria viridis ) (Stilkowski ) and foxtail millet (Wang & Darmency ).…”
Section: Discussionmentioning
confidence: 99%
“…The F 1 hybrids of sprangletop were produced satisfactorily by outcrossing between the resistant and the susceptible genotypes and were screened in the presence of fenoxaprop‐p‐ethyl. The same method has been used in giant foxtail (Volenberg & Stoltenberg ) and black grass (Petersen et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, S. faberi cross resistance to fluazifop-P-butyl was identified in a vegetable cropping system in Wisconsin where the resistant biotype was 10.6-and 319-fold more resistant than the susceptible biotype (Volenberg and Stoltenberg 2002a). Greenhouse experiments have shown that the outcrossing rates between ACCase susceptible and ACCase resistant parent plants are low and range from 0.24 to 0.73% (Volenberg and Stoltenberg 2002b).…”
Section: Herbicide Resistancementioning
confidence: 94%
“…Generally, dry weight production decreases linearly with increases in shade levels (Santelmann et al 1963;Knake 1972). Peak flowering of greenhouse-grown S. faberi plants in Wisconsin occurred 63 to 67 d after planting of seeds (Volenberg and Stoltenberg 2002b). In abandoned fields in Illinois, S. faberi populations showed a bimodal pattern of seed germination where the densities of the populations first peaked in May and then in July/August (Raynal and Bazzaz 1975).…”
Section: Growth and Developmentmentioning
confidence: 99%